(untitled) - Nukariya, Kaiten (London, 1973)
Contents: history of zen in China; History of zen in Japan; The University is the scripture of zen; Buddha, the universal spirit; the nature of man,...
Keywords: Buddha and Buddhism,Đức Phật và Phật giáo